Optimal production, replenishment, delivery, routing and inventory management policies for products with perishable inventory. (January 2019) - Qiu, Yuzhuo; Qiao, Jun; Pardalos, Panos M.
Highlights: A real-world variant of PRP with perishable inventory is introduced. Main inventory management policies are discussed and classified. Three families of valid inequalities are used to tighten the MILP problem. Compare 8 suboptimal delivery and selling priority policies with an optimized policy. Case study shows the applicability of the model and algorithms. Abstract: This paper presents a generalized production-inventory-routing model with perishable inventory. We analyze the optimal integrated decisions of when and how much to deliver and sell products with varying manufacturing periods. We discuss main inventory management policies to demonstrate the applicability of the model in real-world applications for production routing problems (PRPs) with perishable inventory. Furthermore, an exact branch-and-cut algorithm is developed and discussed. We introduce new families of logical, strengthened lot-sizing and lifted Miller–Tucker–Zemlin subtour elimination constraints for the PRP with perishable inventory. Finally, we test the performance of the algorithm. We also implement and compare 8 suboptimal delivery and selling priority policies with an optimized policy to develop managerial implications.